1988
DOI: 10.1111/j.1439-0418.1988.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the biology, phenology and host specificity of Chaetorellia hexachaeta Loew (Dipt., Tephritidae), a possible candidate for the biological control of yellow starthistle (Centautea solstitialis L.)

Abstract: The biology and host specificity of the tephritid Chaetorellia hexachaeta Loew, the larvae of which live in the flower heads of Centaurea solstitialis and some related Centaurea spp. was studied in Northern Greece. The species has at least three generations per year. Previous research revealed that under laboratory conditions adults lived up to 60 days and up to 243 eggs were deposited by a female. Under cage conditions, particularly under oviposition pressure, the threshold of acceptance was lowered and eggs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The first adults to emerge from the overwintered generation do so in April, before yellow starthistle capitula are generally available for oviposition, thus oviposition in this generation of C. australis occurs chiefly on the earlier flowering Centaurea cyanus in Greece (Sobhian & Pittara, 1988). Oviposition by the next two generations (includes overwintering larval progeny) of Chaetorellia australis in Greece occurs on yellow starthistle (Sobhian & Pittara, 1988). White & Marquardt (1989) found intergenerational colour and morphometric differences between the generations that attack Centaurea cyanus versus yellow starthistle in Greece.…”
Section: Establishment and Infestation Frequencymentioning
confidence: 95%
See 4 more Smart Citations
“…The first adults to emerge from the overwintered generation do so in April, before yellow starthistle capitula are generally available for oviposition, thus oviposition in this generation of C. australis occurs chiefly on the earlier flowering Centaurea cyanus in Greece (Sobhian & Pittara, 1988). Oviposition by the next two generations (includes overwintering larval progeny) of Chaetorellia australis in Greece occurs on yellow starthistle (Sobhian & Pittara, 1988). White & Marquardt (1989) found intergenerational colour and morphometric differences between the generations that attack Centaurea cyanus versus yellow starthistle in Greece.…”
Section: Establishment and Infestation Frequencymentioning
confidence: 95%
“…To examine the importance of C. cyanus for Chaetorellia australis, we will continue to monitor fly establishment at yellow starthistle sites with and without Centaurea cyanus, and at yellow starthistle-only sites different distances from sites containing both hosts. In northern Greece, Sobhian & Pittara (1988) reported that Chaetorellia australis infestation frequencies in yellow starthistle ranged from 3 to 17% at five sites without Centaurea cyanus (distances to the nearest C. cyanus sites not provided), and 30 to 47% at three sites also supporting C. cyanus populations.…”
Section: Establishment and Infestation Frequencymentioning
confidence: 98%
See 3 more Smart Citations